2011
DOI: 10.1111/j.1365-313x.2011.04493.x
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary view of functional diversity in family 1 glycosyltransferases

Abstract: SUMMARYGlycosyltransferases (GTs) (EC 2.4.x.y) catalyze the transfer of sugar moieties to a wide range of acceptor molecules, such as sugars, lipids, proteins, nucleic acids, antibiotics and other small molecules, including plant secondary metabolites. These enzymes can be classified into at least 92 families, of which family 1 glycosyltransferases (GT1), often referred to as UDP glycosyltransferases (UGTs), is the largest in the plant kingdom. To understand how UGTs expanded in both number and function during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
284
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(292 citation statements)
references
References 72 publications
(93 reference statements)
5
284
2
1
Order By: Relevance
“…However, the proportion of total UGTs in the Arabidopsis genome that have been functionally characterized remains at <40% (41/112) (Supplemental Data Set 1). There are two explanations for this: (1) The lineage-specific expansion of UGTs and independent acquisition of functions have occasionally led to imprecise prediction only based on the sequence and function of UGTs (Yonekura-Sakakibara and Hanada, 2011). In this study, only UGT74F2 (there are three identified SAGTs, including UGT74F1, UGT74F2, and UGT76B1, in Arabidopsis thus far) had the NAOGT activity.…”
Section: G-e Correlation Analysis Implicated Candidate Genes Involvedmentioning
confidence: 74%
“…However, the proportion of total UGTs in the Arabidopsis genome that have been functionally characterized remains at <40% (41/112) (Supplemental Data Set 1). There are two explanations for this: (1) The lineage-specific expansion of UGTs and independent acquisition of functions have occasionally led to imprecise prediction only based on the sequence and function of UGTs (Yonekura-Sakakibara and Hanada, 2011). In this study, only UGT74F2 (there are three identified SAGTs, including UGT74F1, UGT74F2, and UGT76B1, in Arabidopsis thus far) had the NAOGT activity.…”
Section: G-e Correlation Analysis Implicated Candidate Genes Involvedmentioning
confidence: 74%
“…and Its Two Closely Related Homologs, UGT71B7 and UGT71B8, Lower Cellular ABA Levels Arabidopsis UGTs represent a superfamily containing more than 100 homologs (Ross et al, 2001;LorencKukuła et al, 2004;Yonekura-Sakakibara and Hanada, 2011). Phylogenetic analysis reveals that the Arabidopsis UGT superfamily can be divided into 12 distinct subgroups .…”
Section: Ugt71b6mentioning
confidence: 99%
“…; Ross et al, 2001;Yonekura-Sakakibara and Hanada, 2011). Arabidopsis contains a large number of UGTs.…”
mentioning
confidence: 99%
“…These glycosylation are typically catalyzed by the UDP-glycosyltransferases (UGTs) using uridine 5'-diphosphoglucose (UDP-glucose) as a donor of the sugar moiety [11] [12]. UGTs in plants make up a very diverse group of enzymes that transfer a glucose residue from UDP-glucose to steviol.…”
Section: Introductionmentioning
confidence: 99%